2021
DOI: 10.1080/02673843.2021.1898423
|View full text |Cite
|
Sign up to set email alerts
|

“In this place we have found sisterhood”: perceptions of how participating in a peer-group club intervention benefited South African adolescent girls and young women

Abstract: A combination sexual and reproductive health (SRH) intervention for adolescent girls and young women (AGYW), implemented in South Africa 2016-2019, included facilitated peer-group clubs designed to build AGYW self-esteem, foster supportive peer networks, and provide SRH education. We conducted qualitative in-depth interviews and focus group discussions with AGYW who had participated in peer-group clubs, club facilitators, teachers and intervention implementers. Perceived benefits of participation in peer-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Existing quantitative (23,(43)(44)(45)(46) and qualitative (47-49) studies on adolescent SRH needs in SSA, such as this one, demonstrate the gaps in young people's access to information and resources related to SRH, and provide the basis for the argument that sexuality education must be provided to younger adolescents. Importantly, these findings confirm research from the past decade, highlighting the magnitude of work that remains to be done to more effectively address the SRH needs of ALHIV (42,(50)(51)(52). Recent interventions highlight the importance of family engagement (29, 51, 53), peer-based approaches including peer support groups (8,52), and newer ways of engaging youth, such as mHealth (30,43,49,54).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Existing quantitative (23,(43)(44)(45)(46) and qualitative (47-49) studies on adolescent SRH needs in SSA, such as this one, demonstrate the gaps in young people's access to information and resources related to SRH, and provide the basis for the argument that sexuality education must be provided to younger adolescents. Importantly, these findings confirm research from the past decade, highlighting the magnitude of work that remains to be done to more effectively address the SRH needs of ALHIV (42,(50)(51)(52). Recent interventions highlight the importance of family engagement (29, 51, 53), peer-based approaches including peer support groups (8,52), and newer ways of engaging youth, such as mHealth (30,43,49,54).…”
Section: Discussionsupporting
confidence: 78%
“…With the help of supportive adults who have helped to shape their self-image, some ALHIV felt confident in their ability to make healthy choices around relationships and sexual activity—whether through delaying sexual activity until ready for relationships, or through safer sex and relationship practices. The school and the clinic are crucial mechanisms for the encouragement of sex-positive, well informed, and healthy lifestyles, but often fall short ( 21 , 40 42 ). Systematic training for ALHIV-targeted sexuality education is required to tailor programs to their specific needs.…”
Section: Discussionmentioning
confidence: 99%
“…Oruko et al [18] reported a number of secondary school girls in the same setting, spoke about parental absence or neglect, and our baseline FGDs also suggested some general lack of concern for daughters' welfare, nurturing feelings of low self-worth. Studies that incorporate skills, health education or empowerment have been highly effective in helping to address gender norms, and protect girls from SRH harms [5,58] The narratives emerging inductively from our discussions suggest girls from backgrounds such as rural Kenya would both welcome and benefit from such input.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular concern is the high exposure to sexual and reproductive health (SRH) harms. In SSA these include HIV, (where adolescent girls have twice the rate of new infections compared to adolescent boys), sexually transmitted infections (STIs) and reproductive tract infections (RTIs), female genital mutilation, unsafe abortion and adolescent pregnancy [3][4][5]. Babies born to adolescents are more likely to be preterm, underweight and have a higher risk of dying in infancy [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Sauti ya Vijana (The Voice of Youth) group‐based intervention to address youth mental health challenges in Tanzania proved to be successful in promoting resilience by increasing utilisation of new coping skills, improving relationships and self‐confidence, and reducing stigma in youth living with HIV [32]. A peer group intervention for adolescent girls and young women implemented in South Africa successfully promoted self‐esteem, well‐being and perceived social support, which play a protective role in the sexual and reproductive health of this population [29].…”
Section: Introductionmentioning
confidence: 99%